PENGARUH METODE STORYTELLING TERHADAP KETERAMPILAN BERBICARA SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SD NEGERI 015931 PADANG MAHONDANG - Novena Desrianta Teresia Sitanggang; Bogor Lumbanraja; Patri Janson Silaban; Juliana; Anton Sitepu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effect of using the storytelling method on students' speaking skills in class IV Indonesian at SD Negeri 015931 Padang Mahondang for the 2023/2024 academic year. This research uses quantitative methods, the population of this research is all fourth grade students at SD Negeri 015931 Padang Mahondang. Sampling used a purposive sampling technique and the samples used were 30 class IV students. The average pretest score is 58 while the average posttest score is 85.5 and for the average score on the student questionnaire, the average score is 73.5 with a correlation result of 0.933, which means rcount (0.933) ≥ rtable (0.361), so Ha is accepted. So there is a very strong influence between the use of the storytelling method on the speaking skills of students in class IV of SD Negeri 015931 Padang Mahondang. The results of the t-test research where tcount ≥ ttable is 13.720 ≥ 2.048 so it can be stated that Ha is accepted. This shows that there is a significant positive influence from using the storytelling method on students' speaking skills in class IV of SD Negeri 015931 Padang Mahondang in the 2023/2024 academic year.